A polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel and a preparation method and application thereof

By constructing a non-uniform network with varying crosslinking density gradient and using surfactants to reduce gel surface tension, the problem of insufficient friction coefficient of existing hydrogels at low sliding rates was solved, achieving high mechanical strength and excellent lubrication effect.

CN116731348BActive Publication Date: 2026-11-06ZHEJIANG UNIV OF SCI & TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310702794.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2026-11-06
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

While existing physically cross-linked hydrogels improve mechanical strength, they struggle to achieve a superlubricating friction coefficient (10⁻³ to 10⁻⁴) close to that of biological boundaries at low sliding rates, and existing methods have failed to effectively address this problem.

Method used

A polysaccharide-based multi-network gradient structure preparation method was adopted. Through in-situ gelation of gelatin polymer chains and oxidized starch macromolecular chains, combined with the complexation of sodium alginate and sodium carboxymethyl cellulose with metal ions, a non-uniform network with varying crosslinking density gradient was constructed. Surfactants were introduced to reduce the surface tension of the gel, forming a triple network gradient structure.

Benefits of technology

The prepared hydrogel exhibits good mechanical properties and self-support under high loads, while reducing surface friction, with a friction coefficient reaching 4.6×10-4 and a maximum compressive modulus of 2.25MPa, which is close to the mechanical properties of biological tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116731348B_ABST
    Figure CN116731348B_ABST
Patent Text Reader

Abstract

This invention discloses a method for preparing a polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel, comprising: preparing a homogeneous mixed solution using gelatin, sodium alginate, sodium carboxymethyl cellulose, and a surfactant as raw materials; centrifuging the mixed solution and adding an oxidized starch solution to complex and form a first gradient physical crosslinking network in which the crosslinking density exhibits a gradient change from the circumference to the center in the horizontal direction; and using Ca... 2+ / Fe 3+ Sodium alginate and sodium carboxymethyl cellulose are complexed and crosslinked in a mixed metal ion solution to form a second and third gradient physical crosslinking network in the vertical direction. The hydrogel is then soaked to remove free metal ions until the hydrogel size is stable. This invention also discloses a polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel and its applications. The preparation method of this invention is simple, low-cost, and safe. The prepared hydrogel exhibits excellent mechanical properties and lubrication effects, and has broad application prospects in the biomedical field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of hydrogel materials technology, specifically to a polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel, its preparation method, and its application. Background Technology

[0002] Physically cross-linked hydrogels are less toxic and simpler to prepare than chemically synthesized gels, making them a promising alternative material in tissue engineering. Cellulose-based physically cross-linked hydrogels, in particular, possess suitable extensibility, good flexibility, and excellent permeability to water molecules. Their physical properties are very similar to those of biological tissues, exhibiting a fibrous network microstructure resembling articular cartilage and plant cell walls. They are widely used in biomedical fields such as artificial cartilage, drug delivery systems, and wound dressings.

[0003] Cellulose-based hydrogels have a high water content, and the water is squeezed out under pressure, which can play a role in lubrication and friction reduction. Their structure and properties are similar to articular cartilage, making them a very promising artificial articular cartilage replacement material.

[0004] Single-component physically cross-linked hydrogels (pure cellulose hydrogels, pure gelatin hydrogels, etc.) typically have weak mechanical properties, with compressive moduli generally ranging from tens to hundreds of kilopascals, making it difficult to match the mechanical strength of biological tissues (several to tens of megapascals). Furthermore, the coefficient of friction of physically cross-linked hydrogels is positively correlated with their mechanical strength; an increase in compressive modulus leads to an increase in the coefficient of friction. In other words, there is a contradiction between the mechanical strength requirements of lubricating hydrogels and bioengineering replacement material hydrogels.

[0005] The coefficient of friction for cellulose-based physically cross-linked hydrogels and gelatin-based physically cross-linked hydrogels is typically 10. -1 ~10 -2 It is far from meeting the actual requirement of a low coefficient of friction (10). -3 ~10 -4 Currently, researchers are dedicated to improving the lubricity of hydrogels. For example, highly hydrophilic polymers such as polypyrrolidone (PVP) and acrylamide are introduced into hydrogels to reduce interfacial friction. However, the lubrication effect of hydrogels falls far short of true biological lubrication, especially at low sliding rates, where boundary water lubrication is crucial. Furthermore, simply increasing the hydrophilicity of the gel network backbone leads to a significant decrease in the macroscopic compressive modulus of the gel due to increased water content and larger network chain size, which hinders the widespread application of hydrogels in practical biological scenarios.

[0006] Patent application CN 114870099 A discloses an all-natural polysaccharide-based biodegradable composite bone nail material with an oriented-concentric structure and its preparation method. The invention first prepares an alkaline-soluble CS solution containing HA-CCNC, Alginate, and CCS; after centrifugation, it is heated and gelled in situ to obtain an oriented HA-CCNC / CS / Alginate / CCS hydrogel; after dialysis, it is then... 2+ / Mg 2+ In a mixed solution, bimetallic ions are cross-linked in situ using a gradient permeation process to obtain a concentric circle structure; then, the solution is impregnated with a QCS solution; finally, the solution is transformed into an all-natural polysaccharide-based composite bone nail with an oriented-concentric circle structure through a rotary drying method and a laser threading process.

[0007] The invention patent application with publication number CN 114752077 A discloses a method for preparing a two-component anisotropic hydrogel. This invention mixes two water-soluble hydrogel components (such as cellulose and PVA) that have physical cross-linking effects and dissolves them in water to form a two-component precursor solution, or further reacts chemically to generate chemical bonds to form a cross-linked two-component precursor solution. Then, the two-component precursor solution or the cross-linked two-component precursor solution is directionally frozen. After the precursor solution is completely frozen along the temperature gradient direction, the frozen sample is salted out to obtain a two-component anisotropic hydrogel. The richness of the structural layers improves the comprehensive mechanical properties of the hydrogel. However, none of the above inventions have studied the friction coefficient of the obtained product.

[0008] The invention patent application document with publication number CN 114507408 A discloses a low-friction, modulus-adjustable physical hydrogel, its preparation method and application. Using salt-sensitive polymer monomers, polymers and salt as raw materials, a hydrogel with a rough surface is prepared. Its surface can effectively lock in a low surface energy lubricant, allowing the lubricant to replace air in filling the gel surface. Ultimately, the solid / solid friction between the friction surfaces is transformed into a solid / liquid friction with lower friction force, giving the hydrogel low-friction properties. After the lubricant is injected, the gel sliding angle is about 35 to 48°.

[0009] Patent application CN 114989454 A discloses a method for preparing a multi-network natural polymeric physical hydrogel. The method involves heating and dissolving a thermosensitive polymer in water to form a thermosensitive polymer aqueous solution. While heated, polyanionic polymers are first added to the thermosensitive polymer aqueous solution and stirred until uniformly dispersed. Then, polycationic polymers, an acid-soluble metal compound ion salt, and a lubricant (glycerol) are added to the above mixed solution and stirred until uniformly dispersed, forming a polyelectrolyte thermosensitive mixed sol. The polyelectrolyte thermosensitive mixed sol is poured into a molding container and cooled to transform the liquid thermosensitive mixed sol into a solid state, obtaining a pre-formed hydrogel. Finally, an acidic aqueous solution is poured into a columnar molding container to immerse the gel, resulting in a multi-network natural polymeric physical hydrogel.

[0010] While high-strength or lubricating physically crosslinked hydrogels have been reported, achieving a friction coefficient close to that of superlubricity at biological boundaries at low sliding rates while improving the mechanical strength of physically crosslinked hydrogels remains a challenge. -3 ~10 -4 The problem of articular cartilage with multiple gradient structures has not yet been well resolved, both domestically and internationally. Therefore, inspired by articular cartilage with multiple gradient structures, it is necessary to design multi-network hydrogel matrices with gradient structures to solve the problems existing in the above-mentioned prior art. Summary of the Invention

[0011] To address the problems existing in the prior art, this invention provides a method for preparing a polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel. This method is easy to implement, has mild reaction conditions, and can simultaneously improve the mechanical strength and self-lubricating friction properties of the polysaccharide-based hydrogel. The prepared hydrogel has a multi-network gradient structure, good mechanical strength, and excellent lubrication effect.

[0012] A method for preparing a polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel includes the following steps:

[0013] (1) The first polymer gelatin, the second polymer sodium alginate, the third polymer sodium carboxymethyl cellulose and the surfactant are added to deionized water, dispersed, swollen and stirred to obtain a uniform mixed solution;

[0014] (2) Centrifuge the mixed solution obtained in step (1). During the centrifugation process, add oxidized starch solution to the edge of the mixed solution and gelatin to undergo in-situ gelation to obtain a first physical cross-linked network polysaccharide hydrogel in which the cross-linking density shows a gradient change from the circumference to the center in the horizontal direction.

[0015] (3) Make Ca 2+ / Fe 3+The salt solution diffuses unidirectionally into the interior of the first physical cross-linked network polysaccharide hydrogel prepared in step (2) to construct a non-uniform second and third network with cross-linking density varying with the diffusion direction of metal ions in the vertical direction. The hydrogel is then soaked to remove free metal ions until the size of the hydrogel is stable, resulting in a polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0016] This invention prepares a polysaccharide hydrogel with a first physical cross-linking network, exhibiting a gradient of cross-linking density from the circumference to the center in the horizontal direction, through in-situ gelation of gelatin polymer chains and oxidized starch macromolecular chains. Polysaccharide polymers (sodium carboxymethyl cellulose and sodium alginate) are introduced into this first gradient physical cross-linking network and complexed with metal ions to prepare heterogeneous second and third networks. Specifically, sodium alginate and Ca... 2+ A second-gradient physical cross-linking network is formed through unidirectional diffusion complexation and cross-linking in the vertical direction, with sodium carboxymethyl cellulose and Fe... 3+ The formation of a third-gradient physical cross-linking network through unidirectional diffusion complexation in the vertical direction, along with the introduction of the triple network and the gradient structure with two changing cross directions, can improve the mechanical properties of the polysaccharide-based gel. This allows the hydrogel to have good mechanical properties and maintain self-support under high load pressure. At the same time, the introduction of surfactants can reduce the surface tension of the gel, thereby reducing the friction of the polysaccharide-based multi-network gradient structure physical hydrogel, resulting in a hydrogel with excellent lubrication effect.

[0017] Preferably, in step (1), the gelatin has a weight-average molecular weight of 10,000 to 150,000; the sodium alginate has a weight-average molecular weight of 30,000 to 250,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 0.5 to 1.5; and the sodium carboxymethyl cellulose has a weight-average molecular weight of 3,000 to 3,000,000 and a degree of substitution of 0.6 to 0.9.

[0018] The weight-average molecular weight of gelatin, sodium alginate, and sodium carboxymethyl cellulose should not be too low. Polymers with low weight-average molecular weight are difficult to form a complete three-dimensional network skeleton, resulting in lower gel mechanical strength. Excessively high weight-average molecular weight significantly enhances the viscosity increase caused by chain entanglement, making it difficult to cast the gel presol and introducing more air bubbles, which affects the perfection of the gel's internal structure.

[0019] Preferably, in step (1), the surfactant is a nonionic surfactant or an ionic surfactant.

[0020] The introduction of surfactants into the hydrogel network, with their molecular relaxation behavior differing from that of the network skeleton, endows the gel with excellent lubrication properties. This invention introduces surfactants into a gelatin-sodium alginate-sodium carboxymethyl cellulose blend solution. The surfactants form low surface tension sites on the hydrogel surface, providing an extremely low coefficient of friction, which is beneficial for the application of hydrogel products in artificial joint cartilage replacement materials.

[0021] The hydrophilic portion of the surfactant can form hydrogen bonds with the peptide bonds in gelatin and the carboxyl groups in sodium alginate and sodium carboxymethyl cellulose. The hydrophobic portion of the surfactant is exposed on the hydrogel surface, which reduces the surface tension of the gel. At the same time, the free energy of the hydrophobic portion is higher than that of the three-dimensional network skeleton of the gel. Under sliding shear, the molecular relaxation behavior is significantly different from that of the gel body, thereby reducing the friction of the physically cross-linked hydrogel with dual network gradient structure, providing excellent lubrication performance, and endowing the gel with self-lubricating effect.

[0022] Preferably, the nonionic surfactant includes long-chain fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, fatty acid polyoxyethylene ester, polyoxyethylene alkylamine, polyoxyethylene alkylolamide, or polyether surfactant. More preferably, the nonionic surfactant is sorbitan oleate, sorbitan monolaurate polyoxyethylene (20) ether, or polyoxyethylene dehydrated sorbitan fatty acid ester.

[0023] Preferably, the ionic surfactant includes fatty acid salts, alkyl sulfonates, alkylbenzene sulfonates, amino acid salts, carboxylic acid betaine, sulfobetaine, phosphate betaine, or imidazoline surfactants. More preferably, the ionic surfactant is dodecyl dimethyl hydroxypropyl phosphate betaine, octadecyl hydroxypropyl sulfobetaine, cocoyl carboxymethyl sodium imidazoline acetate, sodium dodecyl sulfate, or sodium dodecylbenzene sulfonate.

[0024] Preferably, in step (1), the mass fraction of gelatin is 0.5-15% based on the mass of the solvent deionized water, the mass fraction of sodium alginate is 0.5-10%, the mass fraction of sodium carboxymethyl cellulose is 0.5-5%, the mass fraction of surfactant is 0.3-1%, and the mass ratio of surfactant to gelatin is 1:1-50.

[0025] Insufficient amounts of gelatin, sodium alginate, and sodium carboxymethyl cellulose make it difficult to form a high-density network structure after polymer chain swelling, and even more difficult to form a complete triple gradient network during subsequent starch oxidative complexation and metal ion crosslinking. Therefore, low amounts of polysaccharide-based polymers cannot synergistically form a double network structure, nor can they provide high-strength support, thus failing to leverage the excellent mechanical properties of the gel matrix. Excessive amounts of polysaccharide-based polymers have two main drawbacks: firstly, they significantly increase the zero-shear viscosity of the mixed solution, making gel casting difficult and leading to problems such as introducing more air bubbles into the gel matrix; secondly, excessive amounts of polysaccharide-based polymers result in too many initial crosslinking sites with the polysaccharide-based polymer chains during metal ion diffusion complexation and crosslinking, leading to an excessively high crosslinking density. Consequently, a dense multi-network gel film forms at the initial contact point between the gel and the metal salt solution, hindering further diffusion of metal ions and impeding the construction of the internal gradient network of the gel.

[0026] If the amount of surfactant is too small, it will not only fail to provide sufficient lubrication, but also cause steric hindrance due to the adsorption and aggregation between the surfactant and the polymer chain, crowding out too many sites for the polymer chain to complex with oxidized starch or metal ions, thus reducing the cross-linking density of the physical cross-linking network. If the amount of surfactant is too large, it will also cause a large number of micelles to remain, increasing the risk of them being released from the gel body during later use and causing damage to the organism.

[0027] Preferably, in step (1), the temperature of the deionized water is 40–60°C.

[0028] The temperature of deionized water should not be too low. At lower temperatures, gelatin cannot swell and dissolve to form a homogeneous solution, which is not conducive to the subsequent preparation of hydrogels. The temperature of deionized water should also not be too high. Sodium alginate is prone to thermal degradation. Sodium alginate solutions with a β-D-mannuronic acid / α-L-guluronic acid ratio of 0.62 will degrade at temperatures above 60°C.

[0029] Preferably, in step (2), the centrifugation speed is 4000-10000 rpm and the time is 5-20 minutes.

[0030] During centrifugation, the centrifugation speed should not be too slow. If the speed is too slow, it will not generate a significant centripetal force, and the added oxidized starch polymer chains will not generate a significant gradient. This will prevent the formation of a first physical cross-linked network polysaccharide hydrogel with a significant cross-linking density gradient from the circumference to the center in the horizontal direction. Conversely, the centrifugation speed should not be too high. If the speed is too high, the centripetal force will be too obvious, the gradient change from the center to the circumference will be too high, and the distribution of the mechanical strength of the hydrogel will be too uneven. Although the high cross-linking density part has excellent mechanical properties, it cannot provide effective support as a whole.

[0031] Preferably, in step (2), the oxidized starch is one of oxidized potato starch, oxidized sweet potato starch, oxidized wheat starch, or oxidized corn starch.

[0032] Preferably, in step (2), the mass fraction of the oxidized starch solution is 0.15-0.5%.

[0033] Preferably, the mass ratio of oxidized starch to gelatin is 5 to 100:1.

[0034] The first physical cross-linking network polysaccharide hydrogel formed by gelatin complexing with oxidized starch exhibits a gradient in cross-linking density from the circumference to the center in the horizontal direction. This first network helps to fix the original size of the gel. The pores formed by the first network bind the surfactant and the polymer chains of sodium alginate and sodium carboxymethyl cellulose, preventing the gel shape from collapsing and components from becoming free during gel soaking. In addition, the gradient in cross-linking density from the center to the circumference results in the mechanical properties of the circumferential region with higher cross-linking density being superior to those of the central region with lower cross-linking density, achieving the effect of a composite material. When a load is applied to the gel, the high cross-linking density region at the edge provides a more significant supporting effect, while the low cross-linking density region in the center maintains a low friction effect.

[0035] Preferably, in step (3), the Ca 2+ / Fe 3+ In salt solutions, Ca 2+ Concentrations range from 0.01 to 0.10 mol / L, Fe 3+ Concentrations range from 0.01 to 0.10 mol / L, Ca 2+ with Fe 3+ The concentration ratio is 10:1 to 1:10.

[0036] polyvalent Ca 2+ and Fe 3+ Compared to monovalent metal ions, they form more coordination bonds with polysaccharide polymers, increasing complexation strength and providing hydrogels with superior mechanical properties.

[0037] Ca 2+ and Fe 3+ The concentration should not be too high; excessively high concentrations of Ca... 2+ With sodium alginate, excessively high concentrations of Fe 3+ If the complexation with sodium carboxymethyl cellulose is too rapid and the crosslinking point density is too high, the second and third networks on the gel surface will be dense and form a film that blocks the diffusion of metal ions, which is not conducive to the establishment of the gradient structure inside the gel. If the metal salt solution with too low a concentration forms too few crosslinking points with the polysaccharide polymer, the second and third networks will be loose, which is not conducive to improving the mechanical strength of the multi-network physically crosslinked hydrogel.

[0038] Preferably, in step (3), the step of making Ca 2+ / Fe 3+ The method for unidirectional diffusion of salt solution into the interior of the first physically cross-linked network polysaccharide hydrogel prepared in step (2) is as follows: the first physically cross-linked network polysaccharide hydrogel prepared in step (2) is placed in Ca 2+ / Fe 3+ Ions can only diffuse into the container from the bottom.

[0039] Specifically, the first physical cross-linked network polysaccharide hydrogel obtained in step (2) is placed in a container with a sealing material on the side and a semi-permeable membrane material on the bottom. The container can ensure that the hydrogel, except for the surface in contact with the semi-permeable membrane material, does not come into direct contact with the metal salt solution. The semi-permeable membrane material can ensure that metal ions can enter the hydrogel body with a lower metal ion concentration from the metal salt solution with a higher metal ion concentration through the semi-permeable membrane material contact surface, so that the metal ion concentration decreases with the diffusion direction. Then, after complexing with sodium alginate and sodium carboxymethyl cellulose, a non-uniform second and third network with cross-linking density changing with the diffusion direction of metal ions in the vertical direction is formed.

[0040] Preferably, in step (3), the temperature of the unidirectional diffusion is 0 to 60°C and the time is 0.5 to 96 hours.

[0041] The unidirectional diffusion time should not be too short, as metal ions will have difficulty entering the gel interior and complexing with the polysaccharide polymer to form a gradient structure within such a short time. The second and third networks cannot be effectively established, resulting in minimal improvement in the gel's mechanical properties. Conversely, the unidirectional diffusion time should not be too long, as excessively long diffusion times cause metal ions to tend to distribute uniformly within the gel, preventing the crosslinking density of the second and third physical networks from exhibiting anisotropy. This results in a polysaccharide-based multi-network gradient structure self-lubricating hydrogel with a high surface modulus, increasing the coefficient of friction and reducing the gel's self-lubricating effect. The diffusion temperature should be matched with the diffusion time; the diffusion time at higher diffusion temperatures should be shorter than the diffusion time at lower diffusion temperatures.

[0042] Preferably, in step (3), the soaking conditions are: soaking in water for 1 to 3 weeks, changing the water multiple times during the period, until the hydrogel reaches a stable equilibrium state.

[0043] This invention also provides a polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared by the above-described method. This polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel possesses both excellent mechanical strength and lubrication effects, and exhibits a friction coefficient close to that of biological boundary superlubricity at low sliding rates.

[0044] This invention also provides the application of the aforementioned polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel in the biomedical field. The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel of this invention dissipates energy through a high-strength gradient matrix to exert its load-bearing function, while enhancing water lubrication through a low-strength surface-coated association structure. It has promising application prospects in the biomedical field, and is particularly suitable for applications such as artificial cartilage and corneas where both mechanical properties and lubrication effects are required.

[0045] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0046] (1) The process steps of the present invention are easy to implement, the reaction conditions are mild, the cost is low, the safety is good, and it is easy to produce on a large scale.

[0047] (2) This invention prepares a first physical cross-linked network polysaccharide hydrogel with a gradient change in cross-linking density from the circumference to the center in the horizontal direction by in-situ gelation of gelatin polymer chains and oxidized starch macromolecular chains. Polysaccharide polymers (sodium carboxymethyl cellulose and sodium alginate) are introduced into the first gradient physical cross-linked network and complexed with metal ions to prepare a non-uniform second and third network. The introduction of the triple network and the gradient structure with two cross-linking directions can improve the mechanical properties of the polysaccharide-based gel, so that the product hydrogel has good mechanical properties and maintains self-support under high load pressure. At the same time, the introduction of surfactant can reduce the surface tension of the gel, thereby reducing the friction of the polysaccharide-based multi-network gradient structure physical hydrogel, so that the prepared hydrogel has excellent lubrication effect.

[0048] (3) The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared by the method of the present invention has a friction coefficient as low as 4.6 × 10⁻⁶ on the glass surface. -4 With a compressive modulus of up to 2.25 MPa, it is quite similar to the mechanical and tribological properties of biological tissues, and has good application prospects in the biomedical field. Attached Figure Description

[0049] Figure 1 This is a schematic diagram of the preparation process of the polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel of the present invention.

[0050] Figure 2 This is a photograph of the polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in Example 1. Detailed Implementation

[0051] The present invention will be further illustrated below with reference to the embodiments and accompanying drawings. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0052] Example 1

[0053] (1) 1% by mass of gelatin (weight average molecular weight 150,000), 1% by mass of sodium alginate (weight average molecular weight 250,000, β-D-mannuronic acid / α-L-guluronic acid ratio 0.5), 1% by mass of sodium carboxymethyl cellulose (weight average molecular weight 3,000,000, degree of substitution 0.6), and 1% by mass of long-chain fatty alcohol polyoxyethylene ether were added to deionized water at 40°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0054] (2) The mixed solution in step (1) is placed in a cylindrical container and centrifuged. During the centrifugation process, 0.2% by mass of the first physical crosslinking agent oxidizes potato starch at the edge of the mixed solution. The oxidized potato starch macromolecular chain undergoes in-situ gelation with gelatin to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0055] (3) At 0℃, 0.01M Ca 2+ and 0.1M Fe 3+ The mixed salt solution was diffused unidirectionally for 96 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibited a gradient from the circumference to the center in the horizontal direction. This was to construct a non-uniform second sodium alginate / Ca alginate hydrogel with a gradient of cross-linking density along the metal ion diffusion direction in the vertical direction. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0056] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 83.9% and a compressive modulus of 0.42 MPa. (See photograph for reference.) Figure 2 As shown. Using a DHR-2 rotational rheometer from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25 °C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 5.5 × 10⁻⁶. -4 In contrast, the compressive modulus of physically cross-linked pure gelatin hydrogel without the addition of long-chain fatty alcohol polyoxyethylene ether was 0.02 MPa, and the coefficient of friction was 7.3 × 10⁻⁶.-2 .

[0057] Example 2

[0058] (1) A first polymer gelatin with a mass fraction of 4% and a weight average molecular weight of 100,000, a second polymer sodium alginate with a mass fraction of 2.5% and a weight average molecular weight of 200,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 0.7, a third polymer sodium carboxymethyl cellulose with a mass fraction of 1.5% and a weight average molecular weight of 1,000,000 and a degree of substitution of 0.65, and a sorbitan oleate with a mass fraction of 0.4% were added to deionized water at 45°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0059] (2) Place the mixed solution in step (1) in a cylindrical container and centrifuge. During the centrifugation process, add 0.4% by mass of the first physical crosslinking agent to the edge of the mixed solution to oxidize sweet potato starch. The oxidized sweet potato starch macromolecular chain and gelatin undergo in-situ gelation to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0060] (3) At 10℃, 0.03M Ca 2+ and 0.08M Fe 3+ The mixed salt solution is diffused unidirectionally for 70 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibits a gradient change from the circumference to the center in the horizontal direction. This is to construct a non-uniform second sodium alginate / Ca2+ hydrogel with a gradient change in cross-linking density along the direction of metal ion diffusion in the vertical direction. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0061] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 77.0% and a compressive modulus of 0.89 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 2.7 × 10⁻⁶. -3In contrast, the compressive modulus of physically cross-linked pure gelatin hydrogel without the addition of long-chain sorbitan oleate was 0.01 MPa, and the coefficient of friction was 1.9 × 10⁻⁶. -1 .

[0062] Example 3

[0063] (1) A first polymer gelatin with a mass fraction of 9.5% and a weight average molecular weight of 80,000, a second polymer sodium alginate with a mass fraction of 5% and a weight average molecular weight of 125,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 1.0, a third polymer sodium carboxymethyl cellulose with a mass fraction of 2.5% and a weight average molecular weight of 800,000 and a degree of substitution of 0.75, and a polyoxyethylene sorbitan fatty acid ester with a mass fraction of 0.47% were added to deionized water at 52°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0064] (2) Place the mixed solution in step (1) in a cylindrical container and centrifuge. During the centrifugation process, add 0.32% by mass of the first physical crosslinking agent to the edge of the mixed solution to oxidize wheat starch. The oxidized wheat starch macromolecular chain and gelatin undergo in-situ gelation to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0065] (3) At 25℃, 0.05M Ca 2+ and 0.06M Fe 3+ The mixed salt solution is diffused unidirectionally for 50 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibits a gradient change from the circumference to the center in the horizontal direction. This is to construct a non-uniform second sodium alginate / Ca2+ hydrogel with a gradient change in cross-linking density along the direction of metal ion diffusion in the vertical direction. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0066] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 74.7% and a compressive modulus of 1.04 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 4.6 × 10⁻⁶. -4 In contrast, the physically cross-linked pure gelatin hydrogel without the addition of polyoxyethylene sorbitan fatty acid esters had a compressive modulus of 0.08 MPa and a coefficient of friction of 9.7 × 10⁻⁶. -2 .

[0067] Example 4

[0068] (1) 12% by mass of gelatin (weight average molecular weight 40,000), 8% by mass of sodium alginate (weight average molecular weight 100,000, β-D-mannuronic acid / α-L-guluronic acid ratio 1.2), 4% by mass of sodium carboxymethyl cellulose (weight average molecular weight 10,000, degree of substitution 0.8), and 1% by mass of dodecyl dimethyl hydroxypropyl phosphate betaine were added to deionized water at 56°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0069] (2) Place the mixed solution in step (1) in a cylindrical container and centrifuge. During the centrifugation process, add 0.2% by mass of the first physical crosslinking agent to the edge of the mixed solution to oxidize corn starch. The oxidized corn starch macromolecular chain and gelatin undergo in-situ gelation to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0070] (3) At 35℃, 0.08M Ca 2+ and 0.03M Fe 3+ The mixed salt solution is diffused unidirectionally for 8 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibits a gradient change from the circumference to the center in the horizontal direction. This is to construct a non-uniform second sodium alginate / Ca2+ hydrogel with a gradient change in cross-linking density along the direction of metal ion diffusion in the vertical direction. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0071] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 84.1% and a compressive modulus of 1.81 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 2.3 × 10⁻⁶. -3 In contrast, the physically cross-linked pure gelatin hydrogel without the addition of dodecyl dimethyl hydroxypropyl phosphate betaine had a compressive modulus of 0.07 MPa and a coefficient of friction of 8.5 × 10⁻⁶. -2 .

[0072] Example 5

[0073] (1) 15% by mass of gelatin with a weight average molecular weight of 10,000, 10% by mass of sodium alginate with a weight average molecular weight of 30,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 1.5, 5% by mass of sodium carboxymethyl cellulose with a weight average molecular weight of 3,000 and a degree of substitution of 0.9, and 0.3% by mass of octadecyl hydroxypropyl sulfobetaine were added to deionized water at 60°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0074] (2) The mixed solution in step (1) is placed in a cylindrical container and centrifuged. During the centrifugation process, 0.15% by mass of the first physical crosslinking agent oxidizing potato starch is added to the edge of the mixed solution. The macromolecular chains of oxidized potato starch undergo in-situ gelation with gelatin to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0075] (3) At 60℃, 0.1M Ca 2+ and 0.01M Fe 3+The mixed salt solution is diffused unidirectionally for 0.5 h into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibits a gradient change from the circumference to the center in the horizontal direction. This is to construct a non-uniform second sodium alginate / Ca2+ hydrogel with a cross-linking density gradient that varies with the direction of metal ion diffusion in the vertical direction. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0076] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 75.3% and a compressive modulus of 2.25 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 8.1 × 10⁻⁶. -4 In contrast, the compressive modulus of physically cross-linked pure gelatin hydrogel without the addition of octadecylhydroxypropyl sulfobetaine was 0.04 MPa, and the coefficient of friction was 4.04 × 10⁻⁶. -2 .

[0077] Example 6

[0078] (1) 2.5% by mass of gelatin (weight average molecular weight 150,000), 1.05% by mass of sodium alginate (weight average molecular weight 250,000, β-D-mannuronic acid / α-L-guluronic acid ratio 0.55), 1.05% by mass of sodium carboxymethyl cellulose (weight average molecular weight 3,000,000, degree of substitution 0.62), and 0.87% by mass of coconut oil-based carboxymethyl sodium imidazoline acetate were added to deionized water at 40°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0079] (2) The mixed solution in step (1) is placed in a cylindrical container and centrifuged. During the centrifugation process, 0.2% by mass of the first physical crosslinking agent oxidizes potato starch at the edge of the mixed solution. The oxidized potato starch macromolecular chain undergoes in-situ gelation with gelatin to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0080] (3) At 5℃, 0.08M Ca 2+ and 0.07M Fe 3+ The mixed salt solution is diffused unidirectionally for 80 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibits a gradient change from the circumference to the center in the horizontal direction. This is to construct a non-uniform second sodium alginate / Ca2+ hydrogel with a gradient change in cross-linking density along the direction of metal ion diffusion in the vertical direction. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0081] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 69% and a compressive modulus of 1.85 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 5.6 × 10⁻⁶. -4 In contrast, the physically cross-linked pure gelatin hydrogel without the addition of sodium carboxymethyl cocoate imidazoline acetate had a compressive modulus of 0.05 MPa and a coefficient of friction of 6.9 × 10⁻⁶. -2 .

[0082] Example 7

[0083] (1) A first polymer gelatin with a mass fraction of 5% and a weight average molecular weight of 100,000, a second polymer sodium alginate with a mass fraction of 2.5% and a weight average molecular weight of 200,000 and a β-D-mannuronic acid / α-L-guluronic acid ratio of 0.5, a third polymer sodium carboxymethyl cellulose with a mass fraction of 1.5% and a weight average molecular weight of 1,000,000 and a degree of substitution of 0.75, and a sodium dodecyl sulfate with a mass fraction of 0.48% were added to deionized water at 48°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0084] (2) Place the mixed solution in step (1) in a cylindrical container and centrifuge. During the centrifugation process, add 0.32% by mass of the first physical crosslinking agent to the edge of the mixed solution to oxidize sweet potato starch. The oxidized sweet potato starch macromolecular chain and gelatin undergo in-situ gelation to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0085] (3) At 28℃, 0.09M Ca 2+ and 0.08M Fe 3+ The mixed salt solution is diffused unidirectionally for 40 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibits a gradient from the circumference to the center in the horizontal direction. This is to construct a non-uniform second sodium alginate / Ca2+ hydrogel with a gradient of cross-linking density in the vertical direction that varies with the direction of metal ion diffusion. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0086] In this embodiment, the prepared polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel has a water content of 63% and a compressive modulus of 1.85 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on the glass surface is only 8.1 × 10⁻⁶. -3 In contrast, the compressive modulus of physically cross-linked pure gelatin hydrogel without the addition of sodium dodecyl sulfate was 0.10 MPa, and the coefficient of friction was 1.3 × 10⁻⁶. -2 .

[0087] Example 8

[0088] (1) 12.5% ​​by mass of gelatin (weight average molecular weight 45,000), 8% by mass of sodium alginate (weight average molecular weight 100,000, β-D-mannuronic acid / α-L-guluronic acid ratio 1.25), 4.2% by mass of sodium carboxymethyl cellulose (weight average molecular weight 10,000, degree of substitution 0.85), and 0.3% by mass of sodium dodecylbenzenesulfonate were added to deionized water at 48°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0089] (2) Place the mixed solution in step (1) in a cylindrical container and centrifuge. During the centrifugation process, add 0.15% by mass of the first physical crosslinking agent to the edge of the mixed solution to oxidize wheat starch. The oxidized wheat starch macromolecular chain and gelatin undergo in-situ gelation to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0090] (3) At 58℃, 0.05M Ca 2+ and 0.1M Fe 3+ The mixed salt solution is diffused unidirectionally for 2 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibits a gradient change from the circumference to the center in the horizontal direction. This is to construct a non-uniform second sodium alginate / Ca2+ hydrogel with a gradient change in cross-linking density along the direction of metal ion diffusion in the vertical direction. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0091] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 65% and a compressive modulus of 1.15 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 3.8 × 10⁻⁶. -3 In comparison, the compressive modulus of physically cross-linked pure gelatin hydrogel without the addition of sodium dodecylbenzenesulfonate was 0.76 MPa, and the coefficient of friction was 2.2 × 10⁻⁶. -2 .

[0092] Example 9

[0093] (1) 14% by mass of gelatin (weight average molecular weight 15,000), 9.5% by mass of sodium alginate (weight average molecular weight 35,000, β-D-mannuronic acid / α-L-guluronic acid ratio 1.3), 3.8% by mass of sodium carboxymethyl cellulose (weight average molecular weight 5,000, degree of substitution 0.85), and 0.5% by mass of long-chain fatty alcohol polyoxyethylene ether were added to deionized water at 50°C, dispersed, swollen, and stirred to obtain a uniform mixed solution.

[0094] (2) Place the mixed solution in step (1) in a cylindrical container and centrifuge. During the centrifugation process, add 0.5% by mass of the first physical crosslinking agent to the edge of the mixed solution to oxidize corn starch. The oxidized corn starch macromolecular chain and gelatin undergo in-situ gelation to obtain a first physical crosslinking network polysaccharide hydrogel in which the crosslinking density shows a gradient change from the circumference to the center in the horizontal direction.

[0095] (3) At 4℃, 0.03M Ca 2+ and 0.03M Fe 3+ The mixed salt solution was diffused unidirectionally for 88 hours into the interior of the first physical cross-linked network polysaccharide hydrogel in step (2), where the cross-linking density exhibited a gradient from the circumference to the center in the horizontal direction. This was to construct a non-uniform second sodium alginate / Ca alginate hydrogel with a gradient of cross-linking density in the vertical direction that varied with the direction of metal ion diffusion. 2+ Network, third sodium carboxymethyl cellulose / Fe 3+ The network is then soaked to remove free metal ions and stabilize the size, resulting in the polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

[0096] The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared in this embodiment has a water content of 73.5% and a compressive modulus of 2.17 MPa. Using a rotational rheometer DHR-2 from TA Instruments (USA), and employing the gel friction test method described in the journal *Journal of Physical Chemistry B* (1999), Vol. 103, No. 29, pp. 6007-6014, "Friction of Gels. 4. Friction on Charged Gels," based on a steady-state friction test mode, under the conditions of a load of 14 kPa, a sliding speed of 0.001 mm / s, and an ambient temperature of 25°C, the coefficient of friction of this polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel on a glass surface was only 6.9 × 10⁻⁶. -3 In contrast, the compressive modulus of physically cross-linked pure gelatin hydrogel without the addition of long-chain fatty alcohol polyoxyethylene ether was 0.18 MPa, and the coefficient of friction was 3.8 × 10⁻⁶.-2 。

Claims

1. A method for preparing a polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel, characterized in that, Includes the following steps: (1) The first polymer gelatin, the second polymer sodium alginate, the third polymer sodium carboxymethyl cellulose and the surfactant are added to deionized water, dispersed, swollen and stirred to obtain a uniform mixed solution; (2) Centrifuge the mixed solution obtained in step (1). During the centrifugation process, add oxidized starch solution to the edge of the mixed solution and gelatin to undergo in-situ gelation to obtain a first physical cross-linked network polysaccharide hydrogel in which the cross-linking density shows a gradient change from the circumference to the center in the horizontal direction. (3) Make Ca 2+ / Fe 3+ The salt solution diffuses unidirectionally into the interior of the first physical cross-linked network polysaccharide hydrogel prepared in step (2) to construct a non-uniform second and third network with cross-linking density varying with the diffusion direction of metal ions in the vertical direction. The free metal ions are then removed by soaking until the hydrogel size is stable, resulting in a polysaccharide-based multi-network gradient structure physical self-lubricating hydrogel.

2. The preparation method according to claim 1, characterized in that, In step (1), the weight-average molecular weight of the gelatin is 10,000 to 150,000; the weight-average molecular weight of the sodium alginate is 30,000 to 250,000, and the ratio of β-D-mannuronic acid to α-L-guluronic acid is 0.5 to 1.5; the weight-average molecular weight of the sodium carboxymethyl cellulose is 3,000 to 3,000,000, and the degree of substitution is 0.6 to 0.9; the surfactant is a nonionic surfactant or an ionic surfactant.

3. The preparation method according to claim 2, characterized in that, The mass fraction of gelatin is 0.5-15% based on the mass of the solvent deionized water, the mass fraction of sodium alginate is 0.5-10%, the mass fraction of sodium carboxymethyl cellulose is 0.5-5%, the mass fraction of surfactant is 0.3-1%, and the mass ratio of surfactant to gelatin is 1:1-50; the temperature of the deionized water is 40-60℃.

4. The preparation method according to claim 1, characterized in that, In step (2), the centrifugation speed is 4000~10000 rpm and the time is 5~20 minutes.

5. The preparation method according to claim 1, characterized in that, In step (2), the oxidized starch is one of oxidized potato starch, oxidized sweet potato starch, oxidized wheat starch or oxidized corn starch, the mass fraction of the oxidized starch solution is 0.15~0.5%, and the mass ratio of oxidized starch to gelatin is 5~100:

1.

6. The preparation method according to claim 1, characterized in that, In step (3), the Ca 2+ / Fe 3+ In salt solutions, Ca 2+ Concentrations range from 0.01 to 0.10 mol / L, Fe 3+ Concentrations range from 0.01 to 0.10 mol / L, Ca 2+ with Fe 3+ The concentration ratio is 10:1 to 1:

10.

7. The preparation method according to claim 1, characterized in that, In step (3), the temperature for unidirectional diffusion is 0~60°C and the time is 0.5~96 hours.

8. The preparation method according to claim 1, characterized in that, In step (3), the soaking conditions are: soaking in water for 1 to 3 weeks, changing the water multiple times during the period, until the hydrogel reaches a stable equilibrium state.

9. The polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel prepared by the preparation method according to any one of claims 1-8.

10. The application of the polysaccharide-based multi-network gradient structure physically self-lubricating hydrogel according to claim 9 in the biomedical field.

Citation Information

Patent Citations

  • Physical hydrogel with low friction and adjustable modulus as well as preparation method and application of physical hydrogel

    CN114507408A

  • Preparation method of two-component anisotropic hydrogel

    CN114752077A

  • All-natural polysaccharide-based degradable composite bone nail material with oriented-concentric circle structure and preparation method of all-natural polysaccharide-based degradable composite bone nail material

    CN114870099A

  • Preparation method of multi-network natural polymer physical hydrogel

    CN114989454A

  • Totally biodegradable short fibre enhanced medical hydrogel body dressing and preparation method thereof

    CN107456602A